Parametric and kinetic study of silicon nitride film deposition on silicon wafer by low pressure chemical vapor deposition (LPCVD) Method - Velasco, Angelito A. (Philippine Engineering Journal)
Silicon nitride films were deposited on silicon wafers by Low Pressure Chemical Vapor Deposition (LPCVD) method. Reaction gases were ammonia and 20 percent silane in nitrogen. The effects of (A) deposition temperature, (B) chamber pressure, (C) NH3-SiH4 flowrate ratio and (D) deposition time on the thickness of the film produced were studied using a full 2k factorial design. The film thickness was found to increase proportionally with temperature, pressure and time, and inversely wit NH3-SiH4 flowrate ratio. Analysis of Variance (ANOVA) shows that all main effects and interactions AC, AD and CD were statistically significant at 99 percent confidence level. An interactive first order model was fitted to the experimental data : Y = 158.46 + 70.39X1 + 26.86X2 - 66.44X2 - 66.44X3 + 74.45 X4 - 29.3 X1 X3 + 33.35 X1 X4 - 30.68 X3 X4 A kinetic study was also conducted in order to determine the rate equation for the growth of silicon nitride on silicon. The computed activation energy was 21.454 kcal/mol, which indicates that the surface reaction is rate limiting. The rate equation was : Deposition rate, nm/min = 37661.7 exp (-4578.5/T). Scanning electron micrographs show that the silicon nitride deposits appear as spherical car shaped clusters. Energy dispersive x-ray (EDX) and x-ray diffraction (XRD) analyses confirm the formation of silicon nitride.